PENGEMBANGAN SUMBER DAYA MANUSIA PERTANIAN PADA ERA DISRUPSI: UPAYA MENDUKUNG AGRIBISNIS INKLUSIF - Herlina Tarigan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
Inclusive and sustainable agribusiness development in the disruption era requires fundamental adaptation. Major changes in community’s activities take place from the real world to virtual activities. One of the urgent needs in inclusive and sustainable agribusiness development is agricultural human resources able to anticipate changes and successfully adapt to those changes. This paper aims to explore changes in the agribusiness order, challenges in the extension system and agricultural human resource development going forward. Scientific review analysis shows that there are physical business cost savings, open and direct new markets, development of internet-based online shop services with smarter, easier, faster, more efficient, and more accurate transaction processes. The agribusiness system requires a new management system with more competitive human resources capacity. Three instruments for developing agricultural human resources are: (1) prioritizing skill improvement and providing infrastructure for information and communication technology (ICT), (2) capability of extension workers and researchers in creating, socializing and implementing inclusive technology with digital literacy, (3) training the farmers with ICT-based production skills, building partnerships, and accessing big data and information in accordance with their current. Accelerating instrument operations needs champions or youth driving agent.